Cardiovascular Computing-Methodologies and Clinical Applications - Golemati, Spyretta; Nikita, Konstantina S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a comprehensive guide to the state-of-the-art in cardiovascular computing and highlights novel directions and challenges in this constantly evolving multidisciplinary field. The topics covered span a wide range of methods and clinical applications of cardiovascular computing, including advanced technologies for the acquisition and analysis of signals and images, cardiovascular informatics, and mathematical and computational modeling.
Cardiovascular signals and images -- Analysis of signals and images -- Cardiovascular informatics -- Signals and telemetry -- Sensing informatics and risk prediction -- Modeling, simulation and system study.
Keywords: Biomedical engineering; Signal processing; Medical informatics; Cardiology; Computer vision; Biomedical Engineering and Bioengineering; Signal, Speech and Image Processing; Health Informatics; Cardiology; Computer Vision